Evidence for Radiation Hormesis after Exposure of Human Lymphocytes to Low Doses of Ionizing Radiation - Kanokporn Noy Rithidech; Bobby R. Scott (SAGE Publishing, 2008)
Previous research has demonstrated that adding a very small gamma-ray dose to a small alpha radiation dose can completely suppress lung cancer induction by alpha radiation (a gamma-ray hormetic effect). Here we investigated the possibility of gamma-ray hormesis during low-dose neutron irradiation, since a small contribution to the total radiation dose from neutrons involves gamma rays. Using binucleated cells with micronuclei (micronucleated cells) among in vitro monoenergetic-neutron-irradiated human lymphocytes as a measure of residual damage, we investigated the influence of the small gamma-ray contribution to the dose on suppressing residual damage. We used residual damage data from previous experiments that involved neutrons with five different energies (0.22-, 0.44-, 1.5-, 5.9-, and 13.7-million electron volts [MeV]). Corresponding gamma-ray contributions to the dose were approximately 1%, 1%, 2%, 6%, and 6%, respectively. Total absorbed radiation doses were 0, 10, 50, and 100 mGy for each neutron source. We demonstrate for the first time a protective effect (reduced residual damage) of the small gamma-ray contribution to the neutron dose. Using similar data for exposure to gamma rays only, we also demonstrate a protective effect of 10 mGy (but not 50 or 100 mGy) related to reducing the frequency of micronucleated cells to below the spontaneous level.